Untangling the Nexus between Human Capital Development and Manufacturing Output in Nigeria - Adamu, Mijinyawa Afebuamhe; Okoh, Johnson I.; Shehu, Araga Abdullahi (NIU Journal of Social Sciences; Vol 11 No 4 (2025): NIU Journal of Social Sciences, Vol. 11 No. 4, December 2025, 2025)
This study investigated the nexus between human capital development and manufacturing sector output in Nigeria over the period 1980–2023. Secondary data obtained from the Central Bank of Nigeria’s Statistical Bulletin were analyzed using the Autoregressive Distributed Lag (ARDL) approach to capture both short-run and long-run relationships. The empirical findings revealed that primary school enrollment had a negative and statistically insignificant effect on manufacturing output, suggesting a misalignment between educational outcomes and the skill requirements of the manufacturing sector. Government expenditures on education and health exhibited positive but statistically insignificant coefficients, indicating that public investment in human capital had not yet translated into measurable productivity gains. In contrast, population growth had a positive and statistically significant impact, highlighting its role in expanding the labor force and market size that stimulated industrial activity. Conversely, life expectancy exerted a negative and significant influence, reflecting demographic pressures such as aging and higher dependency ratios. The study concluded that improving the quality and relevance of human capital development, rather than merely expanding access, was essential for strengthening the link between human capital and manufacturing output in Nigeria. It further recommended targeted education reforms, efficient public health spending, and population management strategies to unlock the productivity potential of the Nigerian manufacturing sector. Keywords: Human Capital Development, Manufacturing sector Output, ARDL model